Basosquamous carcinoma: Dermoscopic clues to diagnosis. Issue 2 (29th August 2016) - Akay, Bengu Nisa; Saral, Secil; Heper, Aylin O.; Erdem, Cengizhan; Rosendahl, Cliff
Abstract: Basosquamous carcinoma (BSC) is a rare skin cancer which has areas of basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) and a transition zone between them. However, dermoscopic features of BSC are not well described in the published work, except one study. The aim of the present study was to better identify and clarify the dermoscopic findings of BSC in the largest group of patients in the published work and to describe its dermoscopic features according to histopathologically BCC‐dominant, SCC‐dominant and intermediate categories. Dermoscopic features of 36 histopathologically proven BSC and their dermatopathological correlates were retrospectively analyzed. Dermoscopic features were evaluated by pattern analysis. Keratin mass (91.7%) was the most common dermoscopic feature. Surface scaling (77.8%), ulceration (69.4%), white structureless areas (69.4%), white clods (66.7%) and blood spots on keratin mass (66.7%) were the other frequent findings. Polymorphous vascular pattern consisting of various combinations of branched, serpentine, straight, coiled or looped vessels were detected in 61% of the lesions. BSC has BCC‐dominant vascular features together with otherwise SCC‐dominant morphology, the common pattern seen in BSC lesions being BCC‐dominant polymorphous or monomorphous vasculature, together with dermoscopic findings of keratinization. White circles, known to be a valuable clue to SCC and keratoacanthoma, were present at the same magnitude in BSC in our study. The observed histological correlation of eosinophilic keratin overlying the epithelium which lined follicular infundibulae in these tumors, provides a plausible new perspective on dermoscopic white circles.